Modifiable Demographic Factors that Differentiate Bronchiolitis from Pneumonia in Nepalese Children Less Than Two Years – A Hospital Based Study - Malla, T; Poudyal, P; Malla, KK (Kathmandu University Medical Journal, 2015)
Background Bronchiolitis and pneumonia is an important cause of mortality and morbidity in children. Various risk factors make these children more prone for this illness. There is limited data on the risk factors from this part of the world. Moreover there is a significant clinical overlap between bronchiolitis and pneumonia thus necessitating the need for evaluating their demographic difference.Objective To evaluate the modifiable demographic risk factors for bronchiolitis and pneumonia in children less than 2 years.Method A prospective, comparative hospital based study undertaken during March 2012- March 2013 in Manipal Teaching Hospital, Pokhara. Altogether 200 cases of bronchiolitis and 200 cases of pneumonia, in the age group of 2 to 24 months, were randomly selected for comparison of risk factors as per a predesigned proforma. A ‘p’ value of